Development of the PBL-STEMR Model on the Earth and Solar System Topic to Enhance Religious Literacy and Metacognitive Knowledge of Madrasah Tsanawiyah (MTs) Students - Kairul Marom; Siti Alimah; Aditya Marianti; Ellianawati Ellianawati; Arif Widiyatmoko (Universitas Negeri Semarang, 2026)
The low integration of religious values in Natural Science (IPA) learning and the suboptimal development of metacognitive knowledge among students of Madrasah Tsanawiyah (MTs) have become issues that require serious attention. Science learning tends to focus on the cognitive aspects of science and separates scientific knowledge from religious values, particularly in the topic of Earth and the Solar System, which actually has a strong connection with religious values. This study aims to develop a Problem Based Learning model integrated with Science, Technology, Engineering, Mathematics, and Religion (PBL-STEMR) and to analyze its feasibility and effectiveness in improving the religious literacy and metacognitive knowledge of MTs students. This research is a Research and Development (R&D) study that refers to the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The product developed is the PBL-STEMR learning model along with its supporting instructional components. The feasibility of the model was tested through expert validation, while the effectiveness of the model was analyzed based on the measurement results of students’ religious literacy and metacognitive knowledge after the implementation of the model. The results of the study indicate that the PBL-STEMR model is considered feasible for use based on expert evaluations. Furthermore, the implementation of the PBL-STEMR model has been proven to be effective in improving the religious literacy and metacognitive knowledge of MTs students in the topic of Earth and the Solar System. This study concludes that the PBL-STEMR model is a feasible and effective innovative approach for integrating science and religious values while enhancing students’ metacognitive knowledge. It is recommended as an alternative for science learning in MTs to support holistic education, balancing scientific understanding and religious character development.